BENTONIT GIL KUKUNINI SORBSION XOSSASINI KIMYOVIY USULDA FAOLLASHTIRISH - Amonov, Muxtor; Izbullayeva, Malika (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
Sorption properties of the powder of processed bentonite clay are investigated. The influence of temperature and time on the sorbent production process was studied. During processing, composites were obtained with the addition of additional components to increase sorption properties.